(untitled) (Bioagro, 2025)
During postharvest storage oca tubers can pass for different stages, in which bioactive compounds can change their content; and specifically the sprouting stage, can alter significatively these components. Therefore, this study evaluated the sprout length, loss weight, reducing sugar content, total phenolics content, and antioxidant capacity of three oca tuber varieties (yellow, purple, and orange) during postharvest storage. Oca tuber varieties were stored at 19 °C ±1 ºC and relative humidity of 85% ±1%. A factorial design was used to evaluate the effect of oca variety and postharvest storage time (0, 15, 30, 45, 60, 75, and 90 days). The sprout length of the three oca varieties begin to growth at 15-30 days of postharvest storage, which indicated that dormancy period was broken, moreover, the sprout length was increased until 90 days of storage. Yellow oca had the longest sprout length (26.4 cm) and the highest loss weight (22.55 %) at 90 days of storage, which indicated an effect of oca variety and postharvest storage time (p value≤0.05). The reducing sugar content, total phenolics content, and antioxidant capacity of the three oca varieties exhibited variable behaviors during storage time and initially oca tubers showed a reduction in their values, which were presumably related to the stabilization period. The postharvest storage time and oca variety produced different physiological changes in the oca tubers, which affect the sprout length, weight loss, reducing sugars, total phenolics content, and antioxidant capacity.